The Potential of Intercropping for Multifunctional Crop Protection in Oilseed Rape (Brassica napus L.) - Emery, Sara E.; Anderson, Peter; Carlsson, Georg; Friberg, Hanna; Larsson, Mattias C.; Wallenhammar, Ann-Charlotte; Lundin, Ola (Frontiers in Agronomy, 2021)
Oilseed rape (OSR; Brassica napus) is a globally important crop which is increasingly under pressure from pests, pathogens and weeds. We investigated the potential of achieving multifunctional crop protection benefits by intercropping oilseed rape with legumes. A field experiment was conducted in which winter oilseed rape was intercropped with the annual frost sensitive legumes berseem clover (Trifolium alexandrinum) or spring faba bean (Vicia faba), or with the winter grain legumes winter faba bean or winter peas (Pisum sativum). We tracked damage to winter oilseed rape by autumn and spring pests (slugs and insects), pathogens, weed biomass, as well as oilseed rape and intercrop yield in each treatment. Intercropping treatments resulted in pest damage that was equivalent or lower than in oilseed rape alone. Follow up field and lab assessments for the frost sensitive legume intercrops provided evidence for a reduction in autumn pest damage to OSR. Each legume intercrop had its own benefits and drawbacks in relation to pest, pathogen and weed suppression, suggesting that the plant species selected for intercropping with oilseed rape should be based on the pests, pathogens and weeds of greatest concern locally to achieve relevant multifunctional benefits. Our study provides a framework for further experiments in which the multifunctional effects of intercropping on pests, pathogens and weeds can be quantified.